A Microgeographic Analysis of Physical Activity Behavior within Elementary School Grounds. Issue 6 (July 2014) - Anthamatten, Peter; Fiene, Erin; Kutchman, Eve; Mainar, Melanie; Brink, Lois; Browning, Ray; Nigg, Claudio R.
Purpose: There is little scholarship on physical activity among children within outdoor spaces and work is needed to advance the design of these spaces from "best practices" towards evidence-based design. This project examined how playground feature density relates to children's physical activity. Design: We used the System for Observing Play and Leisure Activity to observe children's physical activity. Setting: We observed children during school recess on 24 school grounds in the Denver metropolitan area of Colorado, in spring of 2010 and 2011. Subjects: A total of 31, 069 observations were made from an estimated 9900 children aged 5 to 12. These were aggregated and analyzed in 397 playground zones. Measures: We examined utilization, the number of children present in a particular activity zone during an observation, and the percentage of children engaged in moderate to vigorous physical activity as they relate to the density of constructed features on school playgrounds. Analysis: Ordinary least-squares linear regression model assessed the relationship between playground feature density and the utilization and moderate to vigorous physical activity. Results: Significant positive associations were observed between utilization and feature density among all children (β = .20; p < .001) and a statistically significant but small association was observed between moderate to vigorous physical activity and feature density for girls (β = .12; p = .013), but not for boys. Conclusion: This analysis contributes to evidence that design features of play spaces may influence children's behavior within school grounds.